Two new species of Pseudapis Kirby, 1900 (Hymenoptera: Halictidae: Nomiinae) from Oman - Pauly, Alain; Monks, Joseph; Polaszek, Andrew (Zootaxa, 2023)
Two new species are described in the genus Pseudapis: P. kuhlmanni Pauly & Monks, and P. lisetae Pauly & Monks, both from Oman. Their distributional and flower-visiting data are presented, and they are diagnosed and differentiated from other species in the genus.